SYNTHESIS AND PHOTOLUMINESCENCE PROPERTIES OF Eu3+doped Sr2P2O7 PHOSPHORS - Rao, Atchyutha; N., Bujji Babu; Murthy, K.V.R. (International Journal of Research -GRANTHAALAYAH, 2024)
In the present paper, it has been reported that the synthesis and photoluminescence properties of Eu3+doped Sr2P2O7 pyrophosphate phosphors were prepared by conventional solid state reaction method. The rare-earth ion-doped phosphors are significant while considering their stability and solubility. The assimilation of RE3+ activators into single-centered hosts up to complete changeover of entire cations offers the probability to obtain the pretended self-stimulated crystals. The luminescence investigations of a series of such complexes make available much-appreciated statistics in the optical applications. It increases in the activator concentration makes the luminescence materials brighter. Investigations on powder X-ray Diffraction (XRD), SEM, PL and FTIR have been carried out. And also, the luminescence properties such as excitation and emission spectra are determined.